Image of Serbia in textbooks for Serbian as foreign language published at University of Krakow - Mijaljević Katarina G. (University of Kragujevac - Faculty of Pedagogy, Užice, 2019)
The main subject of this paper is a methodical approach applied to the concept of contemporary Serbian reality in a corpus made of textbooks for Serbian as a foreign language published at University of Krakow: A Handbook for Serbian as a Foreign Language (2011) and Live Language Culture (2012). The aim of the paper is to examine the following for each level of knowledge: 1) In what contexts is observed the image of Serbia; 2) what kind of image of Serbia is presented to students. The analysis showed that the authors consistently introduce content that has cultural potential through all levels of learning. It was implemented methodical approach through which students met with Serbia, at the same time comparing Serbian culture with culture of their own country and realized Serbia as part of Europe and the world. The basic level contains mostly conversational style texts, while the intermediate and advanced levels are dominated by authentic informative (publicist and scientific-popular) texts. Activities on texts direct students to look at information about Serbia with many aspects and without cultural stereotypes. It is concluded that the analyzed textbooks illuminate contemporary reality in Serbia from different angles, directing the participants to see all issues in an objective way, which is achieved through analytical reading and various oral and written activities.